The Relationship of Self-Esteem to Depression Incidence in Level 1 Nursing Students - Nur Aulia Majidah; Shinta Prawitasari; Hardin La Ramba (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
Nursing students in their early stages often face academic pressure and psychosocial transitions that can impact their mental health. This study aims to identify the relationship between self-esteem and depression levels among first-year nursing students in Jakarta. A quantitative correlational research method with a cross-sectional approach was used, involving 106 respondents selected through purposive sampling. The instruments used include the Rosenberg Self-Esteem Scale (RSES) to measure self-esteem and the Beck Depression Inventory-II (BDI-II) to assess depression levels. Data analysis was conducted using Spearman's test and chi-square. The results showed a significant negative correlation between self-esteem and depression (ρ = -0.875; p < 0.001), indicating that lower self-esteem is associated with higher levels of depression. These findings emphasize the importance of psychosocial interventions focused on enhancing self-esteem as a preventive measure for depression among nursing students. The study contributes to the development of mental health promotion strategies in nursing higher education. The implications suggest the need to integrate promotive and preventive approaches into the curriculum and counseling services to detect early depression risks and strengthen students' self-esteem from the outset. Group-based interventions and coping skills training can enhance the psychological well-being of students.